Epigenetic and metabolic reprogramming via nanotechnology: a synergistic approach to cancer vaccination in lung tumors - Xu, Min; Zhang, Xialin; Yu, Xinlin; Ma, Cheng; Li, Xinwei; Chen, Gang; Yuan, Gang; Lin, Sheng; Cui, Ran (Frontiers in Genetics, 2025)
Cancer vaccines represent a promising therapeutic modality in immuno-oncology, yet their efficacy is severely constrained within the immunosuppressive microenvironment of lung tumors. Metabolic reprogramming and epigenetic dysregulation are now understood as critical, interconnected determinants that orchestrate tumor microenvironment (TME) immunosuppression and fundamentally shape anti-tumor immune responses. This review comprehensively examines the mechanistic interplay between metabolic reprogramming and epigenetic regulation, and how nanoplatform technologies can be engineered to modulate these axes to augment cancer vaccine efficacy. We analyze advanced nano-delivery system design strategies, the synergistic effects of combining metabolic intervention with epigenetic modification, and their application in overcoming the formidable barriers of the lung TME. By integrating recent advances in nanotechnology, epigenetics, and tumor immunometabolism, we provide critical insights into the development of next-generation cancer vaccines. Furthermore, we propose a novel conceptual framework—The Epi-Met-Immune Synergistic Network—to dissect these interactions and identify key nodes for rational therapeutic intervention, aiming to enhance and sustain durable anti-tumor immunity.